2021
DOI: 10.2478/jtim-2021-0046
|View full text |Cite
|
Sign up to set email alerts
|

Lung adenocarcinoma-specific three-integrin signature contributes to poor outcomes by metastasis and immune escape pathways

Abstract: Background: Inhibitors targeting integrins (ITGs) are applied as a novel strategy for cancers including lung cancer; however, the heterogeneity of ITG subunits might explain why ITG-targeted inhibitors only show limited efficacy for a small group of lung cancer patients. Materials and methods: RNA-Seq data of lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC) patients were obtained from the TCGA database. Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…A number of studies have demonstrated frequent promoter methylation in lung cancer cells, including short stature homeobox gene two (SHOX2), RAS association domain family 1, isoform A (RASSF1A) (6)(7)(8) and homeobox A9 (HOXA9) (9,10). HOXA9 promoter hypermethylation has also been observed in a large proportion of high-grade serous ovarian carcinomas (11).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated frequent promoter methylation in lung cancer cells, including short stature homeobox gene two (SHOX2), RAS association domain family 1, isoform A (RASSF1A) (6)(7)(8) and homeobox A9 (HOXA9) (9,10). HOXA9 promoter hypermethylation has also been observed in a large proportion of high-grade serous ovarian carcinomas (11).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, He et al demonstrated that aberrantly expressed MT1G also affected the immune response of CRC patients ( Peng et al, 2022 ). Immune escape is an important reason for tumor treatment failure and the change of tumor environment caused by ferroptosis may be responsible for it ( Xu et al, 2020 ; Wang et al, 2021 ). According to our results, the ATG7, MAPK9 and MMD were independent ferroptosis-related genes that can used as prognosis markers.…”
Section: Discussionmentioning
confidence: 99%
“…It may have a particular reference value in future tumor differential diagnosis and targeted therapy. Examples include exosomal MiR-155 and MiR-665 as new hepatocellular carcinoma biomarkers (49), and ITGs as indicators of immune escape in NSCLC (50). Tumorrelated markers can be analyzed from multiple perspectives and in multiple dimensions to consider the development of tumors and their prognosis.…”
Section: Discussionmentioning
confidence: 99%